A case report of resolution of acrokeratosis paraneoplastica (Bazex syndrome) post resection of non-small-cell lung carcinoma. (October 2019) - Mititelu, Roxana; Powell, Mathieu
Acrokeratosis paraneoplastica (Bazex syndrome) is a paraneoplastic syndrome frequently associated with squamous cell carcinoma of the aerodigestive tract. We present a case of acrokeratosis paraneoplastica associated with non-small-cell lung carcinoma, which completely resolved once the carcinoma was resected.